2022
DOI: 10.2147/imcrj.s350999
|View full text |Cite
|
Sign up to set email alerts
|

Rectal Cancer Metastasis to the Anal Verge: An Unusual Case Presentation and Review of the Literature

Abstract: Background: Anal metastasis of colorectal adenocarcinoma is very rare, represented by only a handful of case reports in the literature. Previously, reports of metastasis to this region had occurred following a history of anorectal disease, such as anal fistulae. Antecedent trauma to the area from hemorrhoidectomy, fissures, or perineal retractor injury have also been implicated. Case Presentation: Herein we report the case of 69-year-old man without any history of anal disease presenting with a metachronous me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…Colorectal cancer is the third most common cause of cancer-related mortality worldwide and the fourth most common malignancy presenting with metastasis, with 20% of cases presenting with a metastatic disease [ 1 , 2 ]. The most common sites of metastasis are the regional lymph nodes, liver, lungs, and peritoneum; penile involvement, however, is very rare [ 3 , 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Colorectal cancer is the third most common cause of cancer-related mortality worldwide and the fourth most common malignancy presenting with metastasis, with 20% of cases presenting with a metastatic disease [ 1 , 2 ]. The most common sites of metastasis are the regional lymph nodes, liver, lungs, and peritoneum; penile involvement, however, is very rare [ 3 , 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Malignant priapism is a rare phenomenon mostly associated with penile metastasis and has a poor prognosis [ 1 , 2 , 3 , 4 , 5 , 6 ]. The earliest description of penile metastasis dates back to 1870, with the first extensive review published in 1961; between then and 2018, approximately 460 cases were reported, of which 19% originated from a colorectal primary site [ 4 ].…”
Section: Introductionmentioning
confidence: 99%